Anemia, Hepcidin, and Vitamin D in Healthy Preterm Infants: A Pilot Study - Koren, Yael; Lubetzky, Ronit; Mandel, Dror; Ovental, Amit; Deutsch, Varda; Hadanny, Amir; Moran-Lev, Hadar (American Journal of Perinatology, 2021)
Objective The etiology of anemia in premature neonates is multifactorial and may involve anemia of inflammation mediated by hepcidin. Hepcidin expression is suppressed by vitamin D. We aimed to investigate the interrelationship between hepcidin, anemia, and vitamin D status in preterm infants.Study Design Preterm infants aged 1 to 5 weeks were prospectively recruited at the neonatal intensive care unit of the Dana Dwek Children Hospital. Blood counts and serum levels of hepcidin, ferritin, iron, 25-hydroxyvitamin D [25(OH)D] and C-reactive protein (CRP) were measured and compared between anemic and nonanemic preterm infants.Results Forty-seven preterm infants (mean ± standard deviation gestational age at birth 32.8 ± 1.1 weeks, 66% males) were recruited. In total, 36% of the preterm infants were vitamin D deficient [25(OH)D < 20 ng/mL] and 15% were anemic. Hepcidin levels were significantly higher in anemic premature infants than in the nonanemic group (55.3 ± 23.9 ng/mL vs. 30.1 ± 16.3 ng/mL, respectively, p < 0.05). No differences were found in iron, ferritin, 25(OH)D, and CRP levels between anemic and nonanemic premature newborn infants. A positive correlation was found between hepcidin and ferritin (R2 = 0.247, p = 0.02) and a negative correlation was found between 25(OH)D and CRP (R2 = 0.1, p = 0.04). No significant correlations were found between 25(OH)D and hepcidin, iron, ferritin, or CRP.Conclusion Anemia of prematurity was associated with high hepcidin serum levels. The exact mechanisms leading to anemia and the role of vitamin D warrant further investigation.Key Points
Keywords: preterm infants; vitamin D; serum hepcidin; anemia